The figuration of the posthuman child. Issue 6 (1st November 2020) - Lindgren, Therese
ABSTRACT: In a time when the pursuit of quality is high on the Swedish ECEC (Early Childhood Education and Care) policy agenda, teachers' responsibilities for evaluating educational practice, based on documentation of individual children's development and learning, is emphasised. To aid teachers in this work, the Swedish National Agency of Education published a support material promoting 'pedagogical documentation' as a tool and a method for documentation and evaluation, framed within posthumanist theory. From the posthumanist point of view offered in the support material, the traditional Western educational ideal is claimed to fall short of comprehending the transdisciplinary nature and relational complexity of learning as well as the interdependency between the child and the world. In this article, both conditions enabling a posthumanist reconfiguration of the preschool child, as well as the ways in which the child is brought into being as 'posthuman' through policy, research and practice, is examined.